Velhices em jogo? análise sócio-gerontológica de práticas de jogos digitais e não digitais com idosos - Nakamura, Ana Lucia (2020)
This study is composed of the description of the games practices with the elderly in São Paulo day centers, observations, reflections and suggestions, originated from the dialogues with the elderly and managers, caregivers, and the effects noticed from the interactions in the games. In this context, we seek to answer the following question: In the social aspect, what are the results of the practice of activities with digital and non-digital games for healthy elderly people and those with care-dependent older people, or dementias? To answer this question, this study aims to: (i) analyze how the relationship between the elderly person and the instance of playfulness occurs to understand its importance and the sense of playfulness for the elderly; (ii) describe the contributions of digital and non-digital games and identify the types of difficulties of healthy or care-dependent elderly people in practice with games; (iii) identify and describe the gaming experiences and preferences of 60+ players, suggesting game types and ways of playing; (iv) subsidize the development of social and public policies regarding activities that can be applied in the various services aimed at the elderly. The study is carried out through participant observation of the activity with 65 elderly people, in three day centers in São Paulo (SP) in the neighborhoods Bom Retiro, Saúde and Guaianases, from June 2015 to December 2019, totaling 1104 hours of activity . To support this thesis were selected, due to the relevance of their studies on the aging process: teachers Beltrina da P. Pereira da Côrte, Vera Brandão and Flamínia Manzano M. Lodovici, as well as the philosopher Simone de Beauvoir; about the games: professors Sérgio Nesteriuk Gallo and Vicente Martin Mastrocola, researchers Johan Huizinga and Roger Caillois, and the designers of textit game: Katie Salen, Eric Zimmerman and Jane Mcgonigal; about leisure and playfulness: the researcher Manuel Cuenca Cabeza and professor Neuza M. de Matos. As a result, it was found: the creation and strengthening of bonds between the elderly and with care professionals; the increase in social interactions and the time of adherence to the activity, including dependent elderly people; positive changes in players’ self-confidence; perception of skills and discoveries of others; perception of time by the elderly and distance from routine concerns; the social impact that occurred during the development of this study, from the implementation of technological activity with games, replicated in several other day centers, and consequently, the knowledge about the importance of leisure and games with and for the elderly, divided with care professionals, service managers and the community in general